2012
DOI: 10.1093/jxb/ers108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular bases and evolutionary dynamics of self-incompatibility in the Pyrinae (Rosaceae)

Abstract: The molecular bases of the gametophytic self-incompatibility (GSI) system of species of the subtribe Pyrinae (Rosaceae), such as apple and pear, have been widely studied in the last two decades. The characterization of S-locus genes and of the mechanisms underlying pollen acceptance or rejection have been topics of major interest. Besides the single pistil-side S determinant, the S-RNase, multiple related S-locus F-box genes seem to be involved in the determination of pollen S specificity. Here, we collect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 117 publications
2
65
0
2
Order By: Relevance
“…In addition, loss-offunction of the S-RNase results in self-compatibility in both Prunus and Malus (Okada et al 2008;Ferna´ndez i Martı´et al 2009). However, differently from the general inhibition system of Prunus, in the Maloideae the inhibition of S-RNases is thought to be directly triggered by pollen-S genes, each of them providing recognition of a single or a few S-RNases and tartgeting them to degradation; thus, loss-of-function of pollen-S genes leads to opposite results: in Malus, it is expected to extend cross-incompatibility, while it leads to self-compatibility in Prunus (De Franceschi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, loss-offunction of the S-RNase results in self-compatibility in both Prunus and Malus (Okada et al 2008;Ferna´ndez i Martı´et al 2009). However, differently from the general inhibition system of Prunus, in the Maloideae the inhibition of S-RNases is thought to be directly triggered by pollen-S genes, each of them providing recognition of a single or a few S-RNases and tartgeting them to degradation; thus, loss-of-function of pollen-S genes leads to opposite results: in Malus, it is expected to extend cross-incompatibility, while it leads to self-compatibility in Prunus (De Franceschi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the genetic variation of both S-RNase and SFB genes in peach is significantly lower than that of S-RNase and SFB genes in self-incompatible Prunus species. Thus, it seems that S-pistil and S-pollen genes may have coevolutionary relationships (Hegeduˆs and Hala´sz 2007;Vieira et al 2010;De Franceschi et al 2012). The observed low genetic diversity of S-RNase genes may be partially due to self-compatibility in peach.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is thought that multiple pollen S determinants (SLFs) would collaboratively detoxify the non-self S-RNases in the Solanaceae, while a single pollen S determinant (SFB) would release the cytotoxicity of the self S-RNase in Prunus. The role of the pollen S determinant of Pyrinae (SFBBs) is still unclear but it is suggested that the GSI mechanism of Pyrinae would be similar to that of Solanaceae (De Franceschi et al, 2012). On the other hand, three other types of pollen-expressed F-box genes, SLFL1, SLFL2, and SLFL3 (synonymous with the S locus F-box protein with low allelic sequence polymorphism 1, 2, and 3, respectively), were also found on the S locus of Prunus (Entani et al, 2003;Matsumoto et al, 2008;Ushijima et al, , 2004.…”
Section: Pistil Modifiersmentioning
confidence: 99%
“…Thus, this selection is predicted to produce S-heteroallelic pollen grains that are capable of breaking down self-incompatibility by competitive interaction between the two different S factors in the pollen grain (Mase et al 2014). It is an important material for breeding as well as for analyzing the mechanism of competitive interaction, which is now hypothesized to be caused by non-self recognition of S-RNase by two different sets of pollen S-determinants in a single pollen tube (Kubo et al 2010;de Franceschi et al 2012). However, the direct detection of two S-haplotypes in a single pollen grain of a PPM plant has not previously been achieved.…”
Section: Introductionmentioning
confidence: 99%